Corporate Governance dan Struktur Kepemilikan Terhadap Green Banking Disclosure (Studi Pada Perbankan di Indonesia Tahun 2021-2023) - Ulfah, Atika; Denta, Dwi Hajriani (Universitas Palangka Raya, 2025)
The purpose of this study was to examine the impact of independent commissioners and foreign ownership on the green banking disclosures of Indonesian banks in 2021-2023. The population in this study is banking in Indonesia in 2021-2023 and the sample in this study is 35 banks. The sample in this study was obtained by using purposive sampling method. The method used to assess green banking practices is using content analysis that refers to green banking disclosure indicators. Causality relationship between independent board of commissioners and foreign ownership and disclosure of green banking was tested using multiple linear regression analysis method. This study found that there was a significant effect between the independent commissioners on green banking disclosure practices in Indonesian banks and did not find any influence foreign ownership on green banking disclosure practices.